Pergeseran Makna Qat’iy dan Zanniy - Mohamad Ma'mun (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Human social life is always changing along with the change in geography, culture, ideology, and new discoveries in the life sciences community. Of course, it will force the lawyers to respond, because these changes will have implications for the difference and even contrary to the legal texts that have been established. In the Shari’ah for example, The most obvious topic is jarimah hudud, where there is a punishment in the form of hand amputation for thieves and qisas for the killer or about women that must be accompanied by a mahram when traveling. In accordance with the development of the current situation, this punishment is considered to be irrelevant, it has been proven unable to reduce the quantity of the killers as being contrary to the concept of human rights. Regarding the second issue, it is found in the lives of individual freedom to move alone, including women. Thus, it was necessary to be a change in the law to follow social change. Thus, this change also has implications for the field of usul fiqh which has been considered established. Especially in reading of the texts of the nash (Qur’an and Hadith), especially on term qat’iy and zanniy. For this reason, in this paper will be discussed about the shifting of the term qat’iy and zanniy according to the Salaf, Midle, and Contemporary.